2020
DOI: 10.1111/all.14596
|View full text |Cite
|
Sign up to set email alerts
|

Small droplet emission in exhaled breath during different breathing manoeuvres: Implications for clinical lung function testing during COVID‐19

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 8 publications
0
35
0
Order By: Relevance
“…The second study (19) included 33 healthy volunteers who performed different respiratory manoeuvres outside of ultra clean, environment. Like our data they found coughing was the highest aerosol-producing manoeuvre and interestingly they found that increased expiratory flow rates did not increase aerosol production.…”
Section: Discussionmentioning
confidence: 99%
“…The second study (19) included 33 healthy volunteers who performed different respiratory manoeuvres outside of ultra clean, environment. Like our data they found coughing was the highest aerosol-producing manoeuvre and interestingly they found that increased expiratory flow rates did not increase aerosol production.…”
Section: Discussionmentioning
confidence: 99%
“…Nine of the 18 studies provided evidence on endoscopic sinus surgery [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , six studies focused on suctioning for airway clearance [23] , [24] , [25] , [26] , [27] , [28] , four outpatient endoscopy 22 , 23 , 30 , 31 , two nasogastric tube insertion 26 , 27 and one lung function testing 32 . None of the primary studies focused on procedures or testing for dysphagia.…”
Section: Methodsmentioning
confidence: 99%
“…Healthcare workers in Italy were also disproportionally affected with an approximate 20% infection rate, which is significantly higher than that of the general population 271 . Certain activities in contact with patients such as clinical lung function test, due to the emission of small droplets containing viral particles, may convey an additional risk of SARS‐CoV‐2 infection for health workers facing asymptomatic individuals during COVID‐19 due to the emission of small droplets containing viral particles 272 . The relationship between COVID‐19 severity and specific activities in the clinics or other settings that considerably increase the risk of infection warrants further and detailed investigations.…”
Section: Diet and Lifestylementioning
confidence: 99%